Standard isometric contraction has higher reliability than maximum voluntary isometric contraction for normalizing electromyography during level walking among older adults with knee osteoarthritis - Zhu, Xiaoxue; Pang, Yaya; Li, Li; Sun, Wei; Ding, Lijie; Song, Qipeng; Shen, Peixin (Frontiers in Bioengineering and Biotechnology, 2024)
It is a common approach to normalizing electromyography (EMG) with maximum voluntary isometric contraction (MVIC), which may not be suitable for patients with knee osteoarthritis (KOA) since they are often unable or unwilling to develop maximum joint torques due to pain. This study aims to determine the reliability of the standard isometric contraction (SIC) for normalizing EMG among older adults with KOA in comparison with the MVIC. Thirty-five older adults with KOA were recruited. The root mean square of EMG amplitudes from seven muscles of the affected limb during level walking, and during SIC and MVIC tests, were collected. The EMG of the seven muscles during level walking was normalized with SIC and MVIC, respectively. The process was repeated at least one week later. Intra-class correlation coefficients (ICCs) with 95% confidence intervals were calculated to assess the between-and within-day reliabilities. Compared with the MVIC tests, the SIC tests had higher between-(ICC: 0.75-0.86) and within-day (ICC: 0.84-0.95) ICCs in all seven muscles. Compared with normalized with MVIC, the between-(ICC: 0.67-0.85) and within-day (ICC: 0.88-0.99) ICCs were higher in all seven muscles when normalized with SIC. It could be concluded that SIC may have better movement consistency and be more reliable than MVIC for normalizing EMG during level walking among older adults with KOA.